Milk Yield Response of Bypass Protein on Smallholder Dairy Animals - P. Osti, Netra; Jha, P.K; Mandal, P; Shah, B; Shrestha, B.S; Upreti, C.R; Joshi, B.R; Tiwari, M.R (Journal of Buffalo Science, 2018)
Protein need for small holder dairy animals is very limited. Considering this problem one on-station and one on-farm trails were conducted in 2013 and 2014 in Nepal respectively. In on-station trial (2013) 15 milking buffaloes were randomly assigned to 5 dietary treatments (0, 0.5, 1, 1.5 and 2 kg de-oiled soybean meals/day/buffalo) and in on-farm trial (2014), 20 milking buffaloes were assigned to 0.5 kg de-oiled soybean meal/day/buffalo for two months dry period. From on-station trial, significantly higher (42 %) milk production was observed from 0.5 kg and 1 kg de-oiled soybean meal/day/buffalo feeding groups. From the on-farm trials in village dairy buffaloes 20 percent milk production increment was observed compared with the normal farmer's feeding practices (de-oiled soybean meals unfed condition). It was concluded that, in addition to normal diet, 0.5 to 1 kg de-oiled soybean meal (depending up on the body weight of animal and feeding situation) per day feeding as bypass protein sources could be beneficial during dry period where green fodder is scarce to maintain milk production from dairy animals.